ANALISIS VARIASI VORTEX GENERATOR DESAIN FIN AND TUBE HEAT EXCHANGER MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS - Abdul Wasito, (2021)
Fin and tube heat exchanger is a compact heat exchanger that is often used in refrigeration systems. The fluid flow that flows through the fin has a low thermal conductivity compared to the fluid flow that flows through the tube. Low thermal conductivity results in high thermal resistance. Thus, as one of the innovation efforts to improve heat transfer in the heat exchanger, an attempt was made to use a passive method with the addition of a vortex generator to the fin and tube heat exchanger design that produces longitudinal vortex. This causes fluid mixing between the hot fluid and cold fluid which results in an increase in the convection coefficient value. The purpose of this study is to analyze the effect of the longitudinal vortex on the increase in the convection coefficient and pressure drop that occurs. This research was conducted with a numerical simulation approach by varying the shape of the vortex generator in the form of rectangular winglet pairs (RWP), concave rectangular winglet pairs (CRWP) and convex rectangular winglet pairs (CRWP) and angles of attack 5o, 10o, and 15o on 7 rows of tubes. The inlet fluid flow was varied at Reynolds values 284 to 662. The simulation results showed that the maximum convection coefficient increase occurred in the use of the Concave Rectangular Winglet Pairs (CRWP) vortex generator at an angle of attack of 15o and the Reynolds 662 value of 154.13% against the baseline case. Meanwhile, the lowest pressure drop effect occurred in the use of the vortex generator form of Rectangular Winglet Pairs (RWP) at an angle of attack of 5o and Reynolds value of 284 of 45.29% against the baseline case.